Echocardiography and cardiovascular MRI entwined within the imaging domain; uniting the two. A compendium for the echocardiographer. Issue 4 (3rd April 2018) - Shah, Moneal B.; Doyle, Mark; Farah, Victor; Biederman, Robert W. W.
Abstract : A review of the unique and complementary roles echocardiography and cardiovascular MRI provide to the clinician. A focus on the physics of each modality as well as imaging of the left ventricle.